RELASI ETIKA, BISNIS MEDIA, DAN MASYARAKAT TONTONAN YANG DICIPTAKANNYA (Analisis Tayangan Pernikahan Raffi Ahmad-Nagita Slavina) - Hanugraheningtias, Arvinda (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract :Television is one of the most influential medium in today's society. What is considered important by the media (owner), becomes important for the viewers or readers.Television have made people trapped in the imaginations of excessive (hyper-imaginative). Television also creates an instant impression and trying to create a market for his impressions. The mass media play such important role in making the real world as a collection of images that are hypnotic. Television, the major media of popular culture, is perfect for impingement channeling the desire of consumerism and fetishism. Meanwhile, according to Marx and Lukacs there is a conclusion that contemporary society become passive objects that consume anyspectacle. This system does not give priority to use value but the commercial value, so that created goods are fetishes, means that worship 'idols' of the commodity is not departing from the value (use-value) as well as the physical condition of the natural-material objects commodified. Modern society is an infinite accumulation of spectacles. What at first lived has become mere representation. The spectacle is the uniformity and unification of society itself through the images of the display. The reality of life breached its limits by the spectacle, which ones are real and which the spectacle, and the crowd became spectators of their own lives. In fact, when the spectacle become mere representation, then the moment of truth is falsehood.